Peace Education to Manage Institutional Conflict at Addis Ababa University - Yoseph Woubalem Wereta (Cхід, 2019)
The purpose of this research was to investigate conflict in Addis Ababa University (AAU) and thoroughly understand the conflict by identifying related factors: causes, nature and measures taken. Having explored all these factors the purpose extends to recommend peace education as a new intervention to resolve conflict in AAU. As a method of conflict prevention, the author offers the social technology Peace education, which means cultivating values, disseminating knowledge, developing relationships, skills and behavior aimed at achieving peace and harmony with oneself, with others and with the natural environment. The article provides practical advice and guidance on conflict management at universities.